A New East-West Divide? – Immigration and Anti-Immigrant Voting in the 2017 German Parliamentary Election - Kim Leonie Kellermann; Simon Winter (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We empirically examine the relationship between shares of foreigners and shares of votes cast for the Alternative für Deutschland (AfD), the major anti-immigrant party in the 2017 German parliamentary election. The classic theory on the political economy of migration supposes that immigration fosters opposing sentiments among the natives due to fiercer competition for jobs, housing and public goods. Notably, the vote distribution in the 2017 election suggests that AfD vote shares are higher in districts with fewer foreign inhabitants. We exploit administrative data on election results and district-specific features to study a potentially different effect in West and East Germany. Our results for East Germany corroborate the Contact Theory, which states that more intensive exposure to immigration reduces the propensity to anti-immigrant voting. A 10 percentage point increase in the share of foreigners is associated with a 6.3 percentage point decrease in the AfD vote share. By contrast, the contact effect for West Germany is only weak. Additionally, we find evidence for economic competition with aboveaverage unemployment adding to AfD support in both East and West Germany.
Keywords: D72; D91; J15; 330; migration; anti-immigrant parties; contact theory; ethnic competition; economic competition